Extended Versus Narrow-spectrum Antibiotics in the Management of Uncomplicated Appendicitis in Children: A Propensity-matched Comparative Effectiveness Study. Issue 1 (July 2018) - Cameron, Danielle B.; Melvin, Patrice; Graham, Dionne A.; Glass, Charity C.; Serres, Stephanie K.; Kronman, Matthew P.; Saito, Jacqueline M.; Rangel, Shawn J.
Abstract : Objective: The aim of this study was to compare the effectiveness of extended versus narrow spectrum antibiotics in preventing surgical site infections (SSIs) and hospital revisits in children with uncomplicated appendicitis. Summary of Background Data: There is a paucity of high-quality evidence in the pediatric literature comparing the effectiveness of extended versus narrow-spectrum antibiotics in the prevention of SSIs associated with uncomplicated appendicitis. Methods: Clinical data from the ACS NSQIP-Pediatric Appendectomy Pilot Project were merged with antibiotic utilization data from the Pediatric Health Information System database for patients undergoing appendectomy for uncomplicated appendicitis at 17 hospitals from January 1, 2013 to June 30, 2015. Patients who received piperacillin/tazobactam (extended spectrum) were compared with those who received either cefoxitin or ceftriaxone with metronidazole (narrow spectrum) after propensity matching on demographic and severity characteristics. Study outcomes were 30-day SSI and hospital revisit rates. Results: Of the 1389 patients included, 39.1% received piperacillin/tazobactam (range by hospital: 0% to 100%), and the remainder received narrow-spectrum agents. No differences in demographics or severity characteristics were found between groups following matching. In the matched analysis, the rates of SSI were similar between groups [extended spectrum: 2.4% vs narrow spectrum 1.8% (odds ratio, OR: 1.05, 95% confidence interval, 95% CI 0.34–3.26)], as was the rate of revisits [extended spectrum: 7.9% vs narrow spectrum 5.1% (OR: 1.46, 95% CI 0.75–2.87)]. Conclusions: Use of extended-spectrum antibiotics was not associated with lower rates of SSI or hospital revisits when compared with narrow-spectrum antibiotics in children with uncomplicated appendicitis. Our results challenge the routine use of extended-spectrum antibiotics observed at many hospitals, particularly given the increasing incidence of antibiotic-resistant organisms.